Pengaruh Kepuasan Konsumen dan Kepercayaan Merek terhadap Loyalitas Konsumen (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Pengguna sim card IM3 di Universitas Muhammadiyah Surakarta) - Jannah, Roudhotul, Drs. M. Farid Wajdi, MM., Ph.D (2016)
This study aim to determine the effect of consumer satisfaction and brand trust on the customer loyalty of sim card IM3. The independent variables consist of consumer satisfaction and brand trust, meanwhile the dependent variable is customer loyalty. This research was categorized as descriptive quantitative research. The research instrument is in the form of questionaire. The population of this research is the college students of economic and business faculty of Muhammadiyah University of Surakarta in 2012-2016 academic year. The technique of the sample collection was convinience sampling and purpossive sampling method. The samples are taken from 100 college students. The analysis used in this research includes validity test, reliability test, the cassical assumption test, multiple liniear regression analysis, t test, F test, and the coefficient of determination alanysis (R2). The result of the research show that: 1) The consumer satisfaction positively influence the customer loyalty on sim card IM3 in EBF of MUS to the number of (β) 0,520 with significance 0,000. 2) The brand trust positively encourage the customer loyalty on the sim card IM3 in EBF of MUS to the number of (β) 0,245 with significance 0,005, and the adjusted R2 of the consumer satisfaction and brand trust to the customer loyalty on the sim card IM3 in EBF of MUS is 0,639.